PENGEMBANGAN MEDIA CERITA BERGAMBAR BERBASIS CERITA RAKYAT KEDIRI PADA MATERI PENDAPAT PRIBADI ISI BUKU SD - Putri, Septa Rosdiana; Hunaifi, Abdul Aziz; Damariswara, Rian (STKIP Persada Khatulistiwa Sintang, 2024)
The use of engaging and interactive learning media can help students become more enthusiastic and motivated in their learning. This study aims to develop a picture story-based learning media centered on Kediri folklore, which is rich in cultural values. The research method used is the ADDIE research and development model, consisting of the stages of analysis, design, development, implementation, and evaluation. The illustrated folklore learning media was found to meet the criteria for validity, practicality, and effectiveness, with a limited trial yielding a 100% success rate and a broader trial showing 90%, both of which are considered highly effective in learning. This media is concluded to be suitable for elementary school students and also introducing students to local folklore, including stories such as Mount Kelud, Totok Kerot, and the Tale of Calon Arang.